Oral Skills Development Through the Use of Language Learning Strategies, Podcasting and Collaborative Work (GIST – Education and Learning Research Journal, 2017)
This article describes an action research project carried out at a public school in Ibagué, Colombia. Through a qualitative approach, the project aimed to illustrate the impact of using podcasting, language learning strategies and collaborative work in the development of tenth graders’ oral skills. The intervention involved planning, implementing, monitoring and evaluating oral tasks including contextualized and meaningful settings; students’ performance was analyzed with the help of surveys, questionnaires, and the podcasts themselves. The results evidenced how students were positively influenced by these strategies to improve their oral skills.
Keywords: Language learning strategies; metacognition; podcast; collaborative work